The fuzzy inference system approach to a multi-performance characteristic index for surface quality improvement in CNC end milling. (1st January 2011) - Datta, Saurav; Mahapatra, Siba Sankar; Routara, Bharat Chandra; Bandyopadhyay, Asish
Utility embedded fuzzy approach has been adopted for multiple surface quality optimisation of 6061 T4 Aluminium in CNC end milling operation. The purpose is to evaluate the most favourable process environment consisting of selected process parameters viz. spindle speed, feed and depth of cut in order to satisfy multiple requirements of surface integrity. Various surface roughness parameters have been taken into account with a focus to minimise all of them simultaneously. Utility concept has been adopted to convert individual surface roughness parameters into corresponding utility value which have been fed to a fuzzy inference system to obtain a multi-performance characteristic index (MPCI). MPCI has been optimised finally using Taguchi method. Detailed methodology of the proposed approach has been presented with an illustrative example followed by satisfactory result of confirmatory test.